Investigation of mixed mode-I/II fracture problems - Part 2: evaluation and development of mixed mode-I/II fracture criteria - O. Demir; A. O. Ayhan (Fracture and Structural Integrity)
In this study, experimental and numerical results of compact tension shear (CTS) specimen and a new specimen type under in-plane mixed mode (Mode-I/II) loading conditions are compared with existing inplane mixed mode fracture criteria to investigate and understand the nature of fracture behavior properly. The material used in numerical and experimental analyses is Al 7075-T651 aluminum machined from rolled plates in the L-T rolling direction (crack plane is perpendicular to the rolling direction). In Part 1 of the study, results from numerical and experimental analyses are given. Having computed the mixed mode stress intensity factors from the numerical analyses, fracture loads are predicted and compared with different mixed mode-I/II fracture criteria. The experimental and numerical results show that many criteria are in good agreement with each other for predominately mode I to moderate mixed mode conditions. However, existing criteria increasingly differ from the experimental measurements for highly mode-II conditions. Using the computational and experimental results obtained, improved empirical mixed mode I/II fracture criteria for fracture condition and angle are also proposed.